Haematobiochemical alterations in molybdenum-induced hypocuprosis in sheep - RANDHAWA, SWARAN S; RANDHAWA, S S; BRAR, R S (The Indian Journal of Animal Sciences, 2013)
Haematobiochemical alterations in molybdenum-induced hypocuprosis were studied in 6 local bred nondescript sheep. Haematological analysis in hypocuprotic sheep revealed macrocytic normochromic anaemia Biochemical analysis of plasma revealed significant increase in mean plasma, urea, nitrogen and nonsignificant increase in mean plasma copper levels. However, a significant decline was recorded in erythrocytic louperoxide dismutase (ESOD) levels which was associated with nonsignificant alterations in blood glucose and plasma AST, ALT and CPK levels.